Competency-based curriculum mapping as a tool for continuous improvement for Master of Public Administration (MPA) programs - Kapucu, Naim (2017)
Curriculum mapping (CM) is an assessment tool used to articulate and revise an academic curriculum. Network of Schools of Public Policy, Affairs and Administration (NASPAA) accredited graduate programs in public policy, public affairs, and public administration are required to demonstrate a competency-based curriculum development and assessment methods. This article provides the rationale and approach used to generate a competency-based Master of Public Administration (MPA) curriculum and describes a systematic approach to incorporating program learning objectives, stakeholder engagement, competency development or revisions by faculty, into competency-based CM. The competency-based curriculum is relatively new for MPA programs. While there are many potential benefits and challenges, this article focuses on the utility of flexible mission-oriented curriculum design and its ability to link competencies to assessment strategies for MPA programs.
Keywords: Curriculum; Public administration; Competency based teaching